Rural patients' satisfaction with humanistic nursing care in Chinese Public Tertiary Hospitals: a national cross-sectional study - Li, Chuang; Wang, Ning; Zhang, Haixin; Yan, Yongguang; Chen, Huiling; Jiang, Ruxin; Chang, Yulan; Zhao, Pingfan; Cheng, Qiaomei; Song, Bing; Guo, Shujie (Frontiers in Public Health, 2024)
BackgroundThe provision of high-quality healthcare services and patient satisfaction are fundamental objectives in modern healthcare. Humanistic nursing care, which emphasizes empathy, respect for individuality, and cultural sensitivity, aims to build trust and improve the overall experience for patients. This approach is especially relevant for rural patients in China, who often face additional challenges in accessing care in large tertiary hospitals.MethodsA multistage, stratified sampling method was employed to collect data from 8,263 patients aged 18 years or older in large public tertiary hospitals. Humanistic care satisfaction scores were measured using the Nurse Caring Instrument (NCI) questionnaire, a validated tool for assessing patient satisfaction with nursing care.ResultsSatisfaction with nursing humanistic care among rural Chinese patients attending large tertiary public hospitals was low with the overall mean satisfaction score 81.62 ± 16.85. Significant differences in satisfaction were found based on age, marital status, number of children, educational attainment, occupation, monthly household income, department visited, type of medical insurance, and first-time visitor. A multivariate analysis revealed positive correlations with satisfaction for factors such as having children, higher education, higher family monthly income, and first-time visitor, and negative correlations for factors such as older age, being widowed, department visited, and region.ConclusionOlder adults, widowed individuals, and first-time patients expressed lower levels of satisfaction, highlighting the need for tailored interventions. The findings provide insights into the impact of humanistic nursing care for rural patients and emphasize the importance of culturally sensitive approaches to improve patient satisfaction in rural China. This study has several limitations. The cross-sectional design restricts the ability to establish causal relationships, and there is a potential for selection bias, as participants who completed the survey may have higher educational and economic levels, possibly leading to an overestimation of satisfaction. Lastly, as this study focused on rural patients in large public tertiary hospitals in China, the findings may not be generalizable to other settings or patient groups. Future studies should address these limitations for broader applicability and insight.